Using of Wingeom Software in Geometry Learning to Improving the of Mathematical Representation Ability - Fonna, Mutia; Mursalin, M (Universitas Malikussaleh, Aceh Utara, Indonesia, 2018)
The purpose of this study was to determine the use of Wingeom software in geometry learning in the Department of Mathematics Education. This type of research is quasi-experimental. This study examines the use of Wingeom software in geometry learning in the Department of Mathematics Education. The population in this study were all students of the Department of Mathematics Education under the Faculty Education and Teacher Training, Universitas Malikussaleh, and the samples were students of class A1 and class A2. The study was divided into two learning groups, namely the experimental group with the use of Wingeom Software and the control group with ordinary learning. This study begins with an instrument test which shows that (1) Validity indicates that the results are significant, (2) Very high reliability, (3) Good distinguishing power and (4) Moderate difficulty level. To test of homogeneity and normality that the data is homogeneous and normal. Based on the results of calculations using the t test at the significance level Î± = 0.05, obtained tcount of 4.59 with a significance value of 0.003 while the table of 1.68. Because tcount> ttable (3.127> 1.68) and significance <0.05 (0.003 <0.05). Then it can be concluded that the increase in the ability of mathematical representation of students who get learning with the use of Wingeom software is better than the ability of mathematical representation of students who get ordinary learning without Wingeom software.